„Dabitur vobis in illa hora” – Kiegészítések Dr. Huzella Tivadar életrajzához - Magyar, Attila (Gerundium, 2014)
„DABITUR VOBIS IN ILLA HORA” – NOTES TO THE BIOGRAPHY OF TIVADAR HUZELLA. Certain data from the biography of Tivadar Huzella, the anatomy professor of the University of Debrecen, then later one of the Budapest University, are falsely transferred from one essay to another. he book by Imre Törő puts his birthplace to Nagyvárad, however his family was already living and trading in Budapest in 1886, when he was born. he other false information about him is the date of his death: he died on July 11, 1950 at a reserach station established in his property in Alsógöd. Mostly the right date is used, however Imre Törő, Professor of Anatomy and Doctor of Academy for an unkown reason propagates the date of 1951 through his writings about Huzella.